PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG ATAS OBYEK HAK TANGGUNGAN BERDASARKAN NILAI KEADILAN - Taufik Pandan Winoto (Jurnal Indonesia Sosial Sains, 2025)
After the payment for the auction object is made by the buyer to the auction seller, the purpose is to repay the debtor’s debt to the creditor. This study examines the Auction Regulation for the Execution of Guarantee Rights and its alignment with the principles of fairness, focusing on the obstacles faced by auction winners when debtors refuse to vacate the collateral property. The research uses the constructivism paradigm, which views legal science as dealing primarily with laws and regulations. The research approach is social legal research, employing a normative legal research method—also known as literature law research or doctrinal law research—because this study is conducted through library research consisting of legal materials and supported by secondary legal sources. The research findings show that the regulation of the execution of rights of dependents has not been fair due to Article 20 of the Law on the Rights of Dependents and Articles 200 and 224 of the HIR. Article 6 of Law No. 4 of 1996 and the Regulation of the Minister of Finance, as well as Law No. 12 of 2011, are also relevant. Furthermore, weaknesses in the regulations include the contradiction between the legal substance of Article 6 of the HT Law and the explanation of Article 26 of the Law on the Rights of Dependents. The implementation of execution is also based on Article 224 of the HIR.